Immunszintigraphie mit 111ln-DTPA-markierten monoklonalen Antikörpern: Vergleich zwischen ECT und planarer Szintigraphie - Happi, J.; Baum, R. P.; Frohn, J.; Weimer, B.; Halbsguth, A.; Lochner, B.; Brandhorst, I.; Hör, G. (Nuklearmedizin - NuclearMedicine, 1987)
The present study was done in order to examine if the use of111ln-DTPA- labeled MAb fragments in place of 131l-labeled MAb fragments increases the sensitivity of tomographic immunoscintigraphy to reach the level of that of planar imaging techniques. In 11 patients with various primary tumors, local recurrences or metastases [colorectal carcinoma (n = 7), ovarian carcinoma (n = 2), papillary thyroid carcinoma (n = 1), undifferentiated carcinoma of the lung (n = 1)], immunoscintigraphy (IS) was carried out using 111ln-DTPA- labeled F(ab’)2 fragments of various MAbs (anti-CEA, OC 125, anti-hTG) and planar and tomographic imaging were compared intraindividually. By conventional diagnostic procedures, the presence of a tumor mass was confirmed (transmission computer tomography, ultrasound) or verified (131l whole-body scintigraphy, histology) in all cases. Immunoscintigraphy was positive in 9 out of 11 cases by ECT and in 10 out of 11 cases by planar imaging. When using 111 In-labeled MAb fragments, intraindividual comparison of ECT and planar imaging resulted in a similar sensitivity. The increased sensitivity of ECT using this tracer in contrast to 131l-labeled MAb fragments may be attributed to the fact that the physical properties of111 In are much more suitable for the gamma cameras most commonly used (single detector, 3/8” crystal); using 111 In-labeled MAb fragments, count rates sufficient for ECT can be obtained within a reasonable acquisition time. This allows to combine IS with the advantages of ECT regarding tumour localization and prevention of artefacts due to superposition of background.